The Arrangement of an Arabic Dictionary for Ibtida'iyah Students: A Lexicography Perspective - Tika Fadilla; Muhamad Zacky Mubarok; Darsita Suparno (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This study aims to compile an Arabic dictionary that refers to the Arabic language textbook of Madrasah Ibtidaiyah (Al-Lughah Al-Arabiyyah) starting from grades I, II, III, IV, V, and VI which is used as a dictionary for students of Madrasah Ibtidaiyah in the form of a book. This study uses the scientific discipline of Arabic lexicography. The method used in this research is descriptive qualitative method which collects, clarifies and analyzes data in the form of vocabulary without using statistical figures. The translation carried out by researchers uses semantic methods to find out each meaning of the vocabulary. The researchers also uses several supporting dictionaries in translation, including the Al-Munawwir Arabic-Indonesian dictionary, the Al-Ma'any Arabic-Indonesian and Arabic-Arabic dictionary, the contemporary Arabic-Indonesian dictionary (Al-Ashri). The results of this study are in the form of a book-shaped dictionary made using Microsoft Word Program.